FORMULASI DAN EVALUASI SEDIAAN LOTION KOMBINASI EKSTRAK KULIT PISANG (Musa paradisaca L.) DENGAN EKSTRAK KULIT PIR (Pyrus pyrifolia) - Hashary, A Rufaidah; Baso, Fajrul Fhalaq; Wulan, Riska (APDFI (Asosiasi Pendidikan Diploma Farmasi Indonesia), 2025)
Skin is the largest organ in the body, skin damage affects health and appearance, one of the causes of skin damage is free radicals due to ultraviolet radiation. That's why it's important to provide extra protection by using moisturizer or skin cream. The use of lotion that contains antioxidants is good for the skin, one of which is banana peel extract (Musa paradisiaca L) with pear peel extract (Pyrus pyrifolia). This research aims to formulate banana peel extract (Musa paradisiaca L) and a combination of pear peel extract (Pyrus pyrifolia) in formulating and evaluating the physical quality of the preparation. The method used is the experimental method, the extraction process is by maceration using 96% ethanol then a lotion is made from a combination of banana peel extract (Musa paradisiaca L) with pear peel extract (Pyrus pyrifolia) with respective concentrations of FI (1:2), FII (1:1), FIII (2:1), K+ (“M” lotion), and K- (non extract). Preparation testing includes organoleptic tests, homogeneity tests, pH tests, spreadability tests, and moisture tests. From the general observation results, the preparations have a characteristic extract smell, are semi-solid, brownish white in color, have a pH of 8, all preparations are homogeneous, with an average spreadability of 7.1 cm and an average humidity of 45.0.